Toxicological evaluation of Hydrocotyle bonariensis Comm. ex Lamm (Araliaceae) leaves extract - Komla Kaboua; Tcha Pakoussi; Aklesso Mouzou; Mindede Assih; Balakiyém Kadissoli; Komlan Mawubédjro Dossou-Yovo; Patrick Bois (Beni-Suef University Journal of Basic and Applied Sciences, 2021)
Abstract Background The present study was designed to determine the cytotoxic, acute and sub-chronic oral toxicity profile of the hydroethanol extract of Hydrocotyle bonariensis leaves. The toxicity studies are preceded by a phytochemical screening to characterize the phytochemical compounds contained in this extract. Results The phytochemical screening allowed to identify the presence of alkaloids, tannins, flavonoids and saponosids. The cytotoxicity study allowed retaining that this extract does not present cellular toxicity. The acute oral toxicity study was performed at a limit dose of 5000 mg/kg body weight by the oral route. The extract showed no signs of toxicity or mortality during the 14-day daily observation period. Repeated-dose oral toxicity studies were conducted by administering 500 mg/kg and 1000 mg/kg body weight of the extract orally daily to the treated batches for 28 days. The extract did not reveal any toxicity either on the weights of the animals or on the relative weights of the organs taken. The analysis of biochemical and hematological parameters revealed no significant difference between the indicators of the batches treated with 500 mg/kg and 1000 mg/kg, compared to the control batch during the 28 days of treatment. Conclusion These results show that the hydroethanol extract of Hdrocotyle bonariensis leaves is relatively safe toxicologically when administered orally.